MUZAX MEDIA BERHITUNG DI SEKOLAH DASARMUZAX MEDIA BERHITUNG DI SEKOLAH DASAR - Eva Betty; Elvi Mailani; Mastiana Ritonga (Jurnal Guru Kita PGSD, 2019)
Abstract: Muzax Media Numeracy in Primary Schools. The assistance that will be carried out aims to improve the ability of teachers to design and use the "Muzax" Numeracy media in Elementary Schools. The programmed activities will be carried out through several stages, including: (1) assistance in designing and manufacturing "Muzax" media, (2) assistance in using "Muzax" media in the learning process, (3) simulations in the form of lesson study in the use of "Muzax media "In numeracy learning, (4) open class / real teaching use of the media" Muzax "in numeracy learning, (5) monitoring and evaluation, and (6) follow-up. Through the 6 (six) stages of the activities to be carried out, it is hoped that the ability of teachers will increase, especially those related to making “Muzax” media, and their effective use in numeracy learning in elementary schools. Then, the assistance program method will be carried out through several stages, including: (1) preparation, (2) implementation, (3) monitoring and evaluation, and (4) follow-up. Through the methods applied, it should be able to improve the ability of teachers to design and use "Muzax" as an effort to optimize learning to count in elementary school.Keywords: Muzax, Numeracy, Elementary SchoolAbstrak: Muzax Media Berhitung di Sekolah Dasar. Pendampingan yang akan dilakukan bertujuan untuk meningkatkan kemampuan guru dalam merancang dan menggunakan “Muzax” media Berhitung di Sekolah Dasar. Kegiatan yang diprogramkan akan dilakukan melalui beberapa tahapan, di antaranya: (1) pendampingan perancangan dan pembuatan media “Muzax”, (2) pendampingan dalam penggunaan media “Muzax” dalam proses pembelajaran, (3) simulasi dalam bentuk lesson study penggunaan media “Muzax” dalam pembelajaran berhitung, (4) open class/real teaching penggunaan media “Muzax” pada pembelajaran berhitung, (5) monitoring dan evaluasi, dan (6) tindak lanjut. Melalui 6 (enam) tahapan kegiatan yang akan dilakukan, diharapkan kemampuan guru meningkat terutama yang berkaitan dengan pembuatan media “Muzax”, dan penggunaannya secara efektif dalam pembelajaran berhitung di SD. Kemudian, metode program pendampingan akan dilakukan melalui beberapa tahapan, di antaranya: (1) persiapan, (2) pelaksanaan, (3) monitoring dan evaluasi, dan (4) tindak lanjut. Melalui metode yang diterapkan, hendaknya mampu meningkatkan kemampuan guru dalam merancang dan menggunakan “Muzax” sebagai upaya optimalisasi pembelajaran berhitung di SD.Kata Kunci: Muzax, Berhitung, Sekolah Dasar